2020
DOI: 10.1136/bcr-2020-236283
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic multicentric Castleman disease preceded by cutaneous plasmacytosis successfully treated by tocilizumab

Abstract: A woman aged 45 years with a 1.5-year history of violaceous plaques on the forehead and chest presented with fever, weight loss and aggravation of the plaques. Inflammatory markers and interleukin-6 level were elevated, and superficial lymphadenopathies and splenomegaly were identified by CT scan. Immunohistochemical findings of the lymph node and the skin showed polyclonal plasmacytosis and follicular hyperplasia, leading to the diagnosis of idiopathic multicentric Castleman disease (iMCD) after human herpesv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Cutaneous plasmacytosis is characterized by the dermal infiltration of polyclonal mature plasmacytes, and it predominantly affects Asian descent 1 . Although most cutaneous plasmacytosis is indolent, the disease could develop plasma cell type of iMCD 2 . If a patient is diagnosed with cutaneous plasmacytosis, clinicians should carefully follow up with the patient keeping in mind the potential for the development of iMCD.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous plasmacytosis is characterized by the dermal infiltration of polyclonal mature plasmacytes, and it predominantly affects Asian descent 1 . Although most cutaneous plasmacytosis is indolent, the disease could develop plasma cell type of iMCD 2 . If a patient is diagnosed with cutaneous plasmacytosis, clinicians should carefully follow up with the patient keeping in mind the potential for the development of iMCD.…”
Section: Case Presentationmentioning
confidence: 99%
“…1 Although most cutaneous plasmacytosis is indolent, the disease could develop plasma cell type of iMCD. 2 If a patient is diagnosed with cutaneous plasmacytosis,…”
Section: Case Presentationmentioning
confidence: 99%
“…4 Although corticosteroid treatment could provide symptomatic relief, its tapering always leads to recurrence of the skin lesions, which happened in the patient reported by Kamido et al, while a recent study suggested the effectiveness of tocilizumab by targeting IL-6. 3…”
mentioning
confidence: 99%
“…It could precede the development of other systemic features of idiopathic multicentric Castleman disease. 3 Histologically, it may also be reported as 'cutaneous plasmacytosis', which is thought to share a similar pathogenesis with Castleman disease in terms of hypercytokinaemia, in particular interleukin (IL)-6. 4 Although corticosteroid treatment could provide symptomatic relief, its tapering always leads to recurrence of the skin lesions, which happened in the patient reported by Kamido et al, while a recent study suggested the effectiveness of tocilizumab by targeting IL-6.…”
mentioning
confidence: 99%
See 1 more Smart Citation